Int. J. Adv. Res. Biol. Sci 2016
DOI: 10.22192/ijarbs.2016.03.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Determination Of A Pyrethroid Insecticide Deltamethrin Residues In Cattle Meat In Baghdad Province/Al-Rusafa

Abstract: Deltamethrin (DMT) is one of the synthetic pyrethroid compounds having wide insecticidal activity against a large number of ectoparasites and has important uses in veterinary and human health protection. In Iraq DMT has been widely used now in Baghdad and other provinces for sheep, goats and cattle dipping or spraying by the veterinarians and farmers for controlling of ectoparasites in animals and as insecticide in crop production in agricultures. The aims of this study were to determine the levels (ppm) of DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Lambda-cyhalothrin (LCT) is a manufactured pyrethroid insecticide that is being used in home pest control, agriculture, protection of food production and disease vector control [ 33 , 88 ]. LCT has been widely used to control pests, including aphids, Colorado beetles and lepidopteran larvae, [81] and was detected in milk, the blood of dairy cows [ 17 ] and cattle meat [ 43 ]. It has been reported that exposing rats to LCT leads to hepatotoxicity and severe renal structure injury due to its toxicity in rats [ 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lambda-cyhalothrin (LCT) is a manufactured pyrethroid insecticide that is being used in home pest control, agriculture, protection of food production and disease vector control [ 33 , 88 ]. LCT has been widely used to control pests, including aphids, Colorado beetles and lepidopteran larvae, [81] and was detected in milk, the blood of dairy cows [ 17 ] and cattle meat [ 43 ]. It has been reported that exposing rats to LCT leads to hepatotoxicity and severe renal structure injury due to its toxicity in rats [ 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…EL-Shemi and Abou EL-Ella (2015) found that mean residual levels of cypermethrin in tissues of male sheep were 64.2 ±3.05, 12.2 ±0.20 and 62.4 ±3.03 for kidney, liver and muscle, respectively. Moreover Khashan(2016) reported that the levels of deltamethrine pesticide residues in cattle meat samples during October and March were (0.66±0.16µg/kg), and (0.28±0.08µg/kg), respectively. And also Abdu-rrahman (2016) mentioned that mean of DMT (deltamethrin) residues in sheep meat collected from different locations of Sulaimaniya province during June and July was (0.50±0.08µg/kg), (0.99±0.18µg/kg), respectively.…”
Section: Levels Of Organochlorine Residues In Beef and Sheep Tissues mentioning
confidence: 99%